ANALISIS PENGGUNAAN TELEPON SAMBUNGAN LANGSUNG JARAK JAUH SEBAGAI ALTERNATIF FASILITAS KOORDINASI ANTARA PONTIANAK SECTOR DENGAN JAKARTA FIC - Widodo Aris Saputra; Dewi Ratnasari; Siska Wijayanti (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This Airnav Indonesia Pontianak as the provider of air traffic service always keeping their works to increase their great air traffic services that refer to International Civil Aviation Organtization (ICAO) Document 4444 Chapter 10 Transfer Of Coordination which explains about the coordination procedure between the air traffic service units or sector control. The hurdle which have been experienced by Aeronautical Communication Officers (ACO) is The Voice Communication Control System (VCCS) that less than optimal. Those Voice Communication Control System (VCCS) has many problems such as the voice which is really low when the coordination between Pontianak Sector and Jakarta FIC takes place. The second problem is on its output that has really bad quality even it can’t be heard at all. Another problem is a parallel network on Pontianak Sector’s VCCS. Whenever Pontianak Sector calls Jakarta FIC, it will be connected into Jakarta Approach’s VCCS. The method which be used in this research is qualitive descriptive method using 2 variables; Long Distance Direct Dial Phone as the X Variable and coordination between Pontianak Sector and Jakarta FIC as the Y Variable. The data collection technics are using; observation, quetioner, and interview. The purpose of this research is to analyze if the Long Distance Direct Dial Phone could be used as the alternative coordination facility in overcoming the problems that occured on Pontianak Sector’s Voice Communication Control System (VCCS). Hopefully the result of this research could give solutions for Airnav Indonesia Pontianak so they could increase their great work in air traffic services especially in coordination with another sector control.